Early pandemic associations of latitude, sunshine duration, and vitamin D status with COVID-19 incidence and fatalities: A global analysis of 187 Countries. - Reagan M Mogire (PLOS Global Public Health)
In the face of the COVID-19 pandemic, understanding the interplay between environmental factors and virus spread is crucial for global preparedness strategies. This study explores how geographic latitude, sunshine duration, and vitamin D status were associated with the incidence and fatality rates of COVID-19 across 187 countries during the crucial early months of the outbreak. Data on the total number of COVID-19 cases by country were obtained from the COVID-19 Data Repository by the Center for Systems Science and Engineering (CSSE) as of June 30, 2020. Univariate and multivariate regression analyses were conducted to determine the associations between COVID-19 cases and latitude, average hours of sunshine from January to June, and mean 25-hydroxyvitamin D (25(OH)D) levels. The average COVID-19 cumulative incidence and mortality per million population were 2,087 and 69, respectively, with a case fatality rate of 3.19%. COVID-19 case fatality rate was positively associated with latitude (β = 0.030; 95% CI: 0.008, 0.052) and negatively associated with hours of sunshine (β = -1.51; 95% CI: -4.44, 1.41) and 25(OH)D levels (β = -0.054; 95% CI: -0.089, -0.019) in adjusted linear regression analyses. Findings were similar for COVID-19 cumulative incidence and mortality rate. These findings indicate that higher latitude and lower 25(OH)D levels were associated with increased COVID-19 severity and mortality. While the data highlight potential links between vitamin D status and COVID-19 outcomes, causality cannot be inferred.